Pendampingan Penggunaan Canva untuk Membuat Aksi Nyata pada Platform Merdeka Mengajar (PMM) - Yosepha Patricia W. Laja; Lailin Hijriani; Ferdinandus Mone; Yohanis N. Deda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This community service activity (PkM) was carried out based on information on the fact that teachers experienced difficulty in preparing PMM Real Actions and creating real action designs using Canva. Therefore, the aim of this PkM activity is to provide assistance in using Canva to create real PMM actions for teachers at SMPN Neonbat Kefamenanu. The implementation method consists of the preparation stage, implementation stage and evaluation stage. The instruments used were comprehension questionnaires and response questionnaires. The results of the activity showed that there was an increase in the participants' understanding as seen from the average score before the activity of 1.6 to 3.3 after the activity. And there was also 1 real work that was successfully uploaded to the PMM account of one of the participants after participating in this activity. Apart from that, there was a very satisfying response from the activity participants. The conclusion of this PkM activity was that this activity had been successfully carried out, marked by an increase in understanding of the activity participants and a very satisfying response from the participants.